1965
DOI: 10.2172/4495135
|View full text |Cite
|
Sign up to set email alerts
|

SAFETY ANALYSIS REPORT, ADVANCED TEST REACTOR. Volume 1

Abstract: Portions of this document may be illegible in electronic image products. Images are produced from the best available original document. PslnM in %he w t e d Staki?a of AnedCa A W Z e PraaD CleaF-we for Fe@al Scientific and TecSlsPid Xmfcmnakk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Measurements in the ATRC showed that voiding a flux trap and experiment resulted in the maximum accident consequences for a reactivity insertion. The evaluations showed a peak reactor power greater than 10 times normal with an integrated energy of 130 MWsec (1) . The results are shown in Figure 1.…”
Section: Neutronic Analysis a Design Evaluationsmentioning
confidence: 99%
“…Measurements in the ATRC showed that voiding a flux trap and experiment resulted in the maximum accident consequences for a reactivity insertion. The evaluations showed a peak reactor power greater than 10 times normal with an integrated energy of 130 MWsec (1) . The results are shown in Figure 1.…”
Section: Neutronic Analysis a Design Evaluationsmentioning
confidence: 99%